(untitled) (Eternitas: Jurnal Teknik Sipil, 2024)
The higher the number of users of transportation services in urban areas, the more traffic jams in these areas will increase. Sorong City 17 Public Elementary School, is located right on the side of the road where the road is categorized as a Primary Collector road group. The location with the many vehicles that pass through the road, makes the intensity of the noise generated even higher. In educational institutions, what is needed is a calm and comfortable environment. The environment is also a factor that influences the learning concentration of students in receiving lessons. high traffic noise for a long time will cause discomfort. The purpose of this study was to find out the results of noise level analysis and to find out whether students’ learning concentration was affected by the noise generated by vehicle traffic. The calculation method uses CoRTN which is reviewed from the characteristics of land use for the School Area. The results of this study show the time range and location points with the highest noise level of 69.8 dBA at point 1 and the lowest noise value of 61.1 dBA at point 2 which is located on the 2nd floor while based on the noise level questionnaire analysis there are 52% of respondents agree that the noise The high school level interferes with students’ concentration in class.